# Converting Sum or Difference into Product

We will learn how to deal with the formula for converting sum or difference into product.

(i) the sum of two sines into a product of a pair of sine and cosine

(ii) the difference of two sines into a product of a pair of cosine and sine

(iii) the sum of two cosines into a product of two cosines

(iv) the difference of two cosines into a product of two sines

If X and Y are any two real numbers or angles, then

(a) sin (X + Y) + sin (X - Y) = 2 sin X cos Y

(b) sin (X + Y) - sin (X - Y) = 2 cos X sin Y

(c) cos (X + Y) + cos (X - Y) = 2 cos X cos Y

(d) cos (X - Y) - cos (X + Y) = 2 sin X sin Y

(a), (b), (c) and (d) are considered as formulae of transformation from sum or difference to product.

Proof:

(a) We know that sin (X + Y) = sin X cos Y + cos X sin Y ……… (i)

and sin (X - Y) = sin X cos Y - cos X sin Y ……… (ii)

Adding (i) and (ii) we get,

sin (X + Y) + sin (X - Y) = 2 sin X cos Y  ………………..… (1)

(b) We know that sin (X + Y) = sin X cos Y + cos X sin Y ……… (i)

and sin (X - Y) = sin X cos Y - cos X sin Y ……… (ii)

Subtracting (ii) from (i) we get,

sin (X + Y) - sin (X - Y) = 2 cos X sin Y  ………………..… (2)

(c) We know that cos (X + Y) = cos X cos Y + sin X sin Y ……… (iii)

and cos (X - Y) = cos X cos Y - sin X sin Y ……… (iv)

Adding (iii) and (iv) we get,

cos (X + Y) + cos (X - Y) = 2 cos X cos Y  ………………..… (3)

(d) We know that cos (X + Y) = cos X cos Y + sin X sin Y ……… (iii)

and cos (X - Y) = cos X cos Y - sin X sin Y ……… (iv)

Subtracting (iii) from (iv) we get,

cos (X - Y) - cos (X + Y) = 2 sin X sin Y  ………………..… (4)

Let, X + Y = α and X - Y = β.

Then, we have, X = (α + β)/2 and B = (α - β)/2.

Clearly, formula (1), (2), (3) and (4) reduce to the following forms in terms of C and D:

sin α + sin β = 2 sin (α + β)/2 cos (α - β)/2      ………. (5)

sin α - sin β = 2 cos (α + β)/2 sin (α - β)/2  ………  (6)

cos α + cos β = 2 cos (α + β)/2 cos (α - β)/2      ……… (7)

And cos α - cos β = -2 sin (α + β)/2 sin (α - β)/2

⇒ cos α - cos β = 2 sin (α + β)/2 sin (β - α)/2     ……… (8)

Note: (i) Formula sin α + sin β = 2 sin (α + β)/2 cos (α - β)/2 is transform the sum of two sines into a product of a pair of sine and cosine.

(ii) Formula sin α - sin β = 2 cos (α + β)/2 sin (α - β)/2 is transform the difference of two sines into a product of a pair of cosine and sine.

(iii) Formula cos α + cos β = 2 cos (α + β)/2 cos (α - β)/2 is transform the sum of two cosines into a product of two cosines.

(iv) Formula cos α - cos β = 2 sin (α + β)/2 sin (β - α)/2 is transforms the difference of two cosines into a product of two sines.

Converting Product into Sum/Difference and Vice Versa

Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

## Recent Articles

1. ### Constructing a Line Segment |Construction of Line Segment|Constructing

Aug 14, 24 09:52 AM

We will discuss here about constructing a line segment. We know how to draw a line segment of a certain length. Suppose we want to draw a line segment of 4.5 cm length.

2. ### Construction of Perpendicular Lines by Using a Protractor, Set-square

Aug 14, 24 02:39 AM

Construction of perpendicular lines by using a protractor is discussed here. To construct a perpendicular to a given line l at a given point A on it, we need to follow the given procedure

3. ### Construction of a Circle | Working Rules | Step-by-step Explanation |

Aug 13, 24 01:27 AM

Construction of a Circle when the length of its Radius is given. Working Rules | Step I: Open the compass such that its pointer be put on initial point (i.e. O) of ruler / scale and the pencil-end be…

4. ### Practical Geometry | Ruler | Set-Squares | Protractor |Compass|Divider

Aug 12, 24 03:20 PM

In practical geometry, we study geometrical constructions. The word 'construction' in geometry is used for drawing a correct and accurate figure from the given measurements. In this chapter, we shall…